The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Mobilizing Knowledge in Healthcare 2016
DOI: 10.1093/acprof:oso/9780198738237.003.0009
|View full text |Cite
|
Sign up to set email alerts
|

Recovering the Performative Role of Innovations in the Global Travel of Healthcare Practices

Abstract: This chapter discusses the global travel of practices with reference to the international patient safety movement, focusing on a specific approach to incident investigation (Root Cause Analysis or RCA for short). We assess how knowledge of the technique was mobilized, from the United States to Australia, the United Kingdom and beyond. We argue that the mobilization and world spanning circulation of this set of practices was sustained and facilitated by the construction of an "anxiety-reassurance" package. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 0 publications
0
8
0
3
Order By: Relevance
“…This "system" approach to healthcare has been fostered by the release of the "Institute of Medicine (2000)" report in and its numerous follow-up accounts about the importance of improving quality of care through building organization-based systems of quality control and improvement. A striking example is the method of "root cause analysis", a systemized procedure for investigating clinical errors that have quickly spread as an optimal and universal practice of preventing ( future) medical errors as it detects organizational risks and encourages mutual learning (Nicolini et al, 2016). It is generally believed that "best" practices, such as root cause analysis, and subsequent implementation of those best practices in other organizations should guide the way to better and safer care (Zuiderent-Jerak and Berg, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This "system" approach to healthcare has been fostered by the release of the "Institute of Medicine (2000)" report in and its numerous follow-up accounts about the importance of improving quality of care through building organization-based systems of quality control and improvement. A striking example is the method of "root cause analysis", a systemized procedure for investigating clinical errors that have quickly spread as an optimal and universal practice of preventing ( future) medical errors as it detects organizational risks and encourages mutual learning (Nicolini et al, 2016). It is generally believed that "best" practices, such as root cause analysis, and subsequent implementation of those best practices in other organizations should guide the way to better and safer care (Zuiderent-Jerak and Berg, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This is a theme long explored by institutional theorists who trace the flow and adoption of different types of knowledge found internationally. [55][56][57] This review identified some studies where the re-use of ideas was not carried out by taking into consideration the local context. 35 Our findings are also supported by the knowledge mobilisation literature, which suggests that whilst ideas for improvement may easily spread across boundaries, they might not achieve local buy-in and a good 'epistemic fit' within local contexts, especially if there is a lack of knowledge brokering and senior support to encourage organisations to be receptive to the new ideas.…”
Section: Discussionmentioning
confidence: 99%
“…PBE enables better understanding the changing processes in AMP due to different possible interpretations; each of them works as specific objective type that highlights elements concerning power, strategy and conflict -altogether, they regard the practice's locus. Among all possible interpretations, individuals who adopt innovations are not just active, but politically experts (Gherardi & Miele, 2018;Nicolini, Mengis, Meacheam, Waring, & Swan, 2016). The search for innovation in AMP comes from individuals' need (or will) of mimicking one another as the way to seek their own interests (Czarniawska & Sevón, 2005).…”
Section: Practice-based Studies (Pbe)mentioning
confidence: 99%
“…The search for innovation in AMP comes from individuals' need (or will) of mimicking one another as the way to seek their own interests (Czarniawska & Sevón, 2005). Accordingly, the main agents in the innovation process can embody intermediate or mediating roles, whose difference is subtle, although relevant: intermediates are in between, they are neutral innovation carriers, but when they play as mediators, they are active, consequent; thus, they create ties that did not exist before, they change innovation by setting bonds between what is already there and the becoming in order to make the "becoming" more acceptable (Nicolini et al, 2016).…”
Section: Practice-based Studies (Pbe)mentioning
confidence: 99%